Ras participates in the activation of p38 MAPK by interleukin-1 by associating with IRAK, IRAK2, TRAF6, and TAK-1 - O'NEILL, LUKE ANTHONY JOHN (American Society for Biochemistry and Molecular Biology, 2002)
Interleukin-1 (IL-1) activates p38 MAP kinase via the small G protein Ras, and this activity can be down-regulated by another small G protein Rap. Here we have further investigated the role of Ras and Rap in p38 MAPK activation by IL-1. Transient transfection of cells with constitutively active forms of the known IL-1 signaling components MyD88, IRAK, and TRAF-6, or the upstream kinases MKK6 and MKK3, activated p38 MAPK. Dominant negative forms of these were found to inhibit activation of p38 MAPK by IL-1. Dominant negative RasN17 blocked the effect of the active forms of all but MKK3 and MKK6, indicating that Ras lies downstream of TRAF-6 but upstream of MKK3 and MKK6 on the pathway. Furthermore, the activation of p38 MAPK caused by overexpressing active RasVHa could not be inhibited using dominant negative mutants of MyD88, IRAK, or IRAK-2, or TRAF6, but could be inhibited by dominant negative MKK3 or MKK6. In the same manner, the inhibitory effect of Rap on the activation of p38 by IL-1 occurred at a point downstream of MyD88, IRAK, and TRAF6, since the activation of p38 MAPK by these components was inhibited by overexpressing active Rap1AV12, while neither MKK3 nor MKK6 were affected. Active RasVHa associated with IRAK, IRAK2, and TRAF6, but not MyD88. In addition we found a role for TAK-1 in the activation of p38 MAPK by IL-1, with TAK-1 also associating with active Ras. Our study suggests that upon activation Ras becomes associated with IRAK, Traf-6, and TAK-1, possibly aiding the assembly of this multiprotein signaling complex required for p38 MAPK activation by IL-1.
PUBLISHED
Keywords: Biochemistry